Enhancing Students’ Vocabulary Mastery by Using Bingo Game - Nita Amanda Aprilia Nasrun; mujahidah (Inspiring: English Education Journal, 2020)
Nita amanda aprilia. Enhancing Students’ Vocabulary Mastery by Using Bingo Game at the First Grade of SMPN 2 Kulo Kabupaten Sidrap(Supervised by Mujahidah and Ahdar.) Vocabulary is an important factor in all language English teaching. Many methods, strategies and technique had been used by the teacher, lecturers, and instructors in teaching vocabulary. Using Bingo game is suitable for the teacher in teaching vocabulary and it gives solutions for the teacher in teaching learning activities. This reaserch was aimed to see the enhancement of the students’ vocabulary mastery before and after the using of Bingo game on leaerning process. The result of the reaserch are useful for the teacher and students. The teacher should aware that it is important to supplied before teaching make the students more active in learning process. This reaserch was conducted at SMPN 2 Kulo Kabupaten Sidrap the population of this reaserch were the students of class VII Consisted 40 students and the sample of this reaserch were class VII.2 consisted 20 students. The sample was taken by using purposive sampling. The reasercher used pre-test and Post-test to collected the data. Based on data analysis, the researcher found that there is enhancement of the students’ vocabulary mastery at the first grade students of SMPN 2 Kulo Kabupaten Sidrap by using Bingo game, it was indicated by the students mean score of post-test (81.25) was greater than pre-test (51.25). Even, for the level of significant (p) 5% and df=N-1, df= 20-1=19, and the value of t-table 1.729, while the value of t-test is 4.26. it means that the t-test value is greater than t-table value (4.26 ≥ 1.729). Thus, it can be concluded that the students’ vocabulary mastery is significant better after getting treatment. So, the null hypothesis (Ho) is rejected.